Peran Motivasi Kerja dan Efikasi Diri (Self-Efficacy) dalam Meningkatkan Kinerja Karyawan - Hana Diawati; Kokom Komariah; Nor Norisanti (IPM2KPE, 2019)
The purpose of this study was to measure the effect of work motivation and self-efficacy on employee performance at PT. Latanza Sinar Abadi, Sukabumi Regency. The population in this study were employees at PT. Latanza Sinar Abadi, Sukabumi Regency. The research method used is descriptive and associative methods. The sample used in this study is using Simple Random Sampling which is included in probability sampling by distributing 100 questionnaires to employees of PT. Latanza Sinar Abadi, Sukabumi Regency. The analysis technique used is the validity test, reliability test, multiple linear regression analysis, including the coefficient of determination test, multiple correlation coefficients and hypothesis testing using a stimulating test (F test). The results of the study, the test coefficient of determination (R2) of 0.822 can be interpreted that the influence of Work Motivation and Self-Efficacy on Employee Performance is 82.2%. The remaining 17.8% is influenced by other factors not explained in this study. Based on the multiple correlation coefficient test seen from the R value of 0.909, it shows that there is a very strong relationship between work motivation and self-efficacy with employee performance. Based on the F test, get the probability value sig. 0,00 <0,05 which means that together the Work Motivation (X1) and Self-Efficacy (X2) have a significant effect on employee performance (Y). Conclusions, work motivation and self-efficacy have a positive and significant effect on employee performance Keywords: Work Motivation, Self-Efficacy, Employee Performance.